PEMODELAN KEWIRAUSAHAAN BERBASIS WEB PADA TEKNOLOGI BUDIDAYA TANAMAN KRPL (KAWASAN RUMAH PANGAN LESTARI) DI KOTA PEKALONGAN - Ari Handriatni (LPPM Universitas Pekalongan, 2019)
The Sustainable Food Home Area Model is a breakthrough alternative to agricultural development to realize food diversification or diversification consisting of tuber crops, vegetables, fruits, toga, livestock and fisheries. Support and fulfillment of household food in diverse, nutritious and safe food consumption patterns, so that the model is expected to provide decent welfare, play a real role in economic growth and equity, support regional and especially rural development through a local resource approach. Empowering communities to build sustainable food home areas in their homes and neighborhoods will greatly help a family provide family food through the use of agricultural innovation technology. Successful implementation of the sustainable food home area is realized in one Neighborhood Association, Community Unit, Village or Village that has applied the principle of sustainable food houses by adding intensification of utilization of living fences, village roads and public facilities, green open land, as well as developing processing, marketing the results and meeting the needs of production facilities Web-based. Modeling is better known as web-based agribusiness. The yields in the form of vegetables, tubers, fruit and toga are not only consumed for household needs, marketing to meet the needs of cafes, restaurants and hotels, to meet the needs of production facilities using the web. fellow KRPL group members in the city of Pekalongan have used WhatsApp Group and facebook